Building for the mind a neuro-architectural approach of spatial experience for sustainable mental health and wellbeing - Alaa Akmal Elghor; Zeinab Shafik; Atef Abdel-Moneim Ali; Mennat-Allah Elhusseiny (Renewable Energy and Sustainable Development, 2024)
Purpose With the growing recognition of the significance of sustainable development and promoting good health and wellbeing, sustainable development and mental health are still newly integrated in the scientific literature. This research aims to highlight the potential of neuro-architecture, which is an interdisciplinary field that studies the relationship between the built environment, cognitive neuroscience and psychology, of enabling architects to gain more scientific-based studies to understand the biological and sensory effect of built environments on our brains for sustainable mental health. Design/ methodology This is a quantitative deductive experimental research adopting comparative neuroscientific approach to measure the impact of form of space boundaries on animal model where form of space boundaries is the only changed parameter and the only variable. This is attained by conducting behavioural assessment and biological tests. Data is analysed statistically using ANOVA & Dunkin. Findings Behaviour assessment using the Y-Maze test demonstrated that mice housed in curvilinear space had strong working memory that indicates intact prefrontal cortical performance. Also, biological tests results showed a significant increase in formation of antioxidants in spaces with curvilinear boundaries. These findings promote that curvilinear forms not only have an aesthetic and psychological preference but also can have neurological enriching impact over a long period of time on brain health. Practical implications          This research sheds light on the multidisciplinary approach of architecture and urban design. The science-based method adopted clarifies that architects and urban designers can seek evidence using scientific tools and including scientific approaches in design decisions. Creating inspiring spaces which affect the users moods, health and well-being can be easily verified using experimentation. Thus, sustainable design is not limited to applying surficial strategies, but also can be included into actual evaluation based on biological variations. Thus, sustainable architecture and wellbeing can be proven scientifically to inform architects and designers regarding a revolutionary approach in designing spaces. Originality We confirm that the research is our original work, and that all the assistance received and resources have been acknowledged, and we are responsible of its content and authenticity.   Received: 23 May 2024 Accepted: 26 June 2024 Published: 01 September 2024